Effect of Workplace Stress on Job Performance - Azman Ismail; Noorshafine Saudin; Yusof Ismail; Ainon Jauhariah Abu Samah; Rizal Abu Bakar; Norish Norsiah Aminudin (Economic Review: Journal of Economics and Business, 2015)
The study examines the relationship between workplace stress and job performance. A survey method was employed to gather self-administered questionnaires from executive and non-executive employees of a leading private investment bank in Peninsular Malaysia. The outcomes of SmartPLS path model analysis of the data showed two important findings: firstly, physiological stress was positively and significantly correlated with job performance. Secondly, psychological stress was positively and significantly correlated with job performance. This finding reveals that physiological and psychological stresses act as important predictors of job performance in the studied organization. The paper provides discussion, implications and conclusion.
Keywords: M10; M12; L8; 330; Physiological stress; Psychological stress; Job performance